2006
DOI: 10.1128/aem.00109-06
|View full text |Cite
|
Sign up to set email alerts
|

Selecting Lactic Acid Bacteria for Their Safety and Functionality by Use of a Mouse Colitis Model

Abstract: Studies showed that specific probiotics might provide therapeutic benefits in inflammatory bowel disease. However, a rigorous screening of new probiotics is needed to study possible adverse interactions with the host, particularly when intended for administration to individuals with certain health risks. In this context, the objective of this study was to investigate the role of three lactobacilli (LAB) on intestinal inflammation and bacterial translocation using variations of the mouse model of 2,4,6-trinitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
71
1
7

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(81 citation statements)
references
References 48 publications
2
71
1
7
Order By: Relevance
“…Based on the same mechanism as lactulose, pH modulation was observed with all tested L. plantarum strains into the colon, but not into the ileum, probably due the poor survival of L. plantarum during the passage through the stomach and the duodenum. 40 Experiments performed in our laboratory where treatment was administered orally, intrarectally, or by both routes showed that only the last two conditions produced a beneficial effect on blood ammonia levels (data not shown), suggesting that in loco colonic administration is sufficient to reduce ammonia. Enumeration of Lactobacillus confirmed a very low number of CFU (Ͻ10 3 CFU/mL) inside the stomach and the small intestine after oral administration, maybe due to strong acidic conditions and presence of pepsin and lysozyme.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the same mechanism as lactulose, pH modulation was observed with all tested L. plantarum strains into the colon, but not into the ileum, probably due the poor survival of L. plantarum during the passage through the stomach and the duodenum. 40 Experiments performed in our laboratory where treatment was administered orally, intrarectally, or by both routes showed that only the last two conditions produced a beneficial effect on blood ammonia levels (data not shown), suggesting that in loco colonic administration is sufficient to reduce ammonia. Enumeration of Lactobacillus confirmed a very low number of CFU (Ͻ10 3 CFU/mL) inside the stomach and the small intestine after oral administration, maybe due to strong acidic conditions and presence of pepsin and lysozyme.…”
Section: Discussionmentioning
confidence: 99%
“…qPCRs were conducted as previously described [10,11] . For characterization of the fecal microbiota PCR primers were designed targeting B. lactis according to Gueimonde and co-workers [17] .…”
Section: Analysis Of Microbiota By Quantitative Real-time Pcr (Qrt-pcr)mentioning
confidence: 99%
“…Thus we chose to study the effects of selected probiotic bacteria in allergic rhinitis in children during the birch pollen season. The specific strains used in this study were selected based on their anti-inflammatory properties and an expected effect in promoting a Th1 type of immune response [11,12] . The study population was chosen to cover subjects with confirmed birch pollen allergy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6] LAB have a positive stimulus on ingestion and the immune system. [7] LAB are reported for non-specific activation of the host's defense system.…”
mentioning
confidence: 99%